2023
DOI: 10.1515/psr-2022-0242
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of propene selectivity and yield in the dehydrogenation of propane via process simulation approach

Abstract: Propene is a vital feedstock in the petrochemical industry with a vast range of applications. And there is a continuous rise in propene demand. To gain insight into how the on-purpose method could help meet the demand in the propene market, we investigated the impact of temperature (T) and pressure (P) on product distribution in terms of product yield and selectivity using the process simulation approach. Existing related studies were deployed to identify possible products that could be evaluated in the simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…To help address all the aforementioned issues, this report presents the ndings made for the comparison of freeware and commercial process simulators in the simulation of ethane dehydrogenation to produce ethylene using the Gibbs minimization approach [30][31][32][33]. The study further demonstrated how temperatures and pressure in uence ethane conversion and ethylene yield in dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…To help address all the aforementioned issues, this report presents the ndings made for the comparison of freeware and commercial process simulators in the simulation of ethane dehydrogenation to produce ethylene using the Gibbs minimization approach [30][31][32][33]. The study further demonstrated how temperatures and pressure in uence ethane conversion and ethylene yield in dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%